Population study of laternula truncata (bivalvia: anomalodesmata: laternulidae) in the mangrove sand flat of kungkrabaen bay, thailand, with notes on laternula cf. corrugata - Prezant, R.; Sutcharit, C.; Chalermwat, K.; Duangdee, Teerapong (Proceedings of the International Marine Bivalve Workshop, Chanthaburi, Thailand, 2008)
Overall benthic macroinvertebrate biodiversity, along with laternulid density, was higher closer to mangroves but relative infaunal invertebrate dominance increased along a transect that transcended a hummock closer to the mangrove forest, across an open sand fl at, and terminated in another isolated humMock farther from the fringing forest. A population of the anomalodesmatan bivalve Laternula truncata (Lamarck, 1818) was examined in a mangrove sand fl at in Kungkrabaen Bay, Thailand, to determine population size, cohort distribution, and basic relationships with sediment and infaunal macroinvertebrate biodiversity. Relatively high densities of L. truncata were found in muddy sands, often deeply buried in or close to tangled rootlet mats of the mangrove trees Avicennia alba Blume, 1827, and A. marina (Forsskal) Vierhapper, 1907, along isolated mangrove hummocks. They were less common in open areas of the mangrove fl at. This population of L. truncata was relatively evenly distributed across size classes, minus the smallest sizes, suggesting continuous recruitment with a possible loss of recent recruits or recruitment. Overall benthic macroinvertebrate biodiversity, along with laternulid density, was higher closer to mangroves but relative infaunal invertebrate dominance increased along a transect that transcended a hummock closer to the mangrove forest, across an open sand fl at, and terminated in another isolated hummock farther from the fringing forest. A nearby population of L. cf. corrugata (Reeve, 1863) inhabited a distinctly different habitat. Laternula cf. corrugata was shallowly buried and dwelt in the mangrove forest proper among different species of mangroves and in sandier sediments. Behavioural observations of both laternulids indicated that both were capable of reburying, with smaller specimens more rapidly, albeit still slowly, succeeding in full re-entry into the sediment. Larger specimens of L. truncata were incapable of reburial. Morphological, ecological, and behavioural distinctions between L. truncata and L. cf. corrugata are considered in light of their habitat differences, confusion within laternulid systematics, and diffi culty in resolving the taxonomy of the latter species.
Keywords: dept.aa; ⛔ No DOI found

The use of hi fidelity simulation to enhance nursing students' therapeutic communication skills - Sleeper, J.A.; Thompson, C. (International Journal of Nursing Education Scholarship, 2008)
Nursing students entering psychiatric settings for clinical practice need a solid foundation of therapeutic communication skills. This article presents an innovative strategy for nursing students to practice therapeutic communication skills with psychiatric patients by using hi fidelity simulation with Laerdal SimMan. Using the SimMan vocal function enabled nurse educators to develop communication algorithms that allowed students to interact with SimMan as they would with psychiatric patients. The SimMan algorithms can be designed to mimic many scenarios typically found in psychiatric settings. Nursing students can use this technology to take the therapeutic communication skills they have learned in the classroom and practice them in a safe laboratory environment before entering actual psychiatric settings. The ability of students to practice communication skills prior to entering psychiatric settings can promote effective therapeutic communication skills and decrease student anxiety. Copyright ©2008 The Berkeley Electronic Press. All rights reserved.
Keywords: Communication; Psychiatric patients; SimMan; Teaching strategies; dept.aa